2018
DOI: 10.3390/ijerph15061230
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Future Parents on Infant Feeding Intentions and Its Association with Breastfeeding Duration: Results from the Growing Up in New Zealand Cohort Study

Abstract: Maternal intentions are believed to have the strongest influence on infant feeding. However, what has rarely been studied, are the associations of maternal and partner intentions, and the influence these factors have on infant feeding. Our objective was to describe breastfeeding intentions of pregnant women and their partners, agreement about these intentions, and whether this agreement is associated with breastfeeding initiation and duration. This study was completed within the Growing Up in New Zealand study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In Vietnam, the involvement of fathers in breastfeeding promotion programs could increase the early breastfeeding initiation rate, as well as exclusive breastfeeding at 4 and 6 months [ 44 , 58 ]. In other countries, women with supportive partners or sharing parenting support were more likely to intend to breastfeed [ 19 , 20 , 22 , 24 , 25 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vietnam, the involvement of fathers in breastfeeding promotion programs could increase the early breastfeeding initiation rate, as well as exclusive breastfeeding at 4 and 6 months [ 44 , 58 ]. In other countries, women with supportive partners or sharing parenting support were more likely to intend to breastfeed [ 19 , 20 , 22 , 24 , 25 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that many factors can affect breastfeeding intentions. These factors include parity, previous breastfeeding experience [15,[19][20][21], seeing other women breastfeed [22,23], having a supportive partner [19,20,22,24,25], not living with any family-in-law [20], breastfeeding knowledge [26][27][28], and having a positive attitude and beliefs regarding the benefits of breastfeeding [20,22]. Each of these are modifiable factors that health practitioners can target to improve breastfeeding rates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, less decision-making power is usually associated with less maternal motivation or even more mental health problem [ 35 ], which will hinder the mother to overcome the challenges associated with breastfeeding, such as continuing breastfeeding when encounter breast pains. Finally, unlike making decisions alone, more participants in a decision-making process may follow with more time to make decision, more disagreements and more inconsistent actions after decision, which may lead to worse consequence [ 6 , 46 ]. Additional research is need to exam the above possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…High intention and self-efficacy increase the likelihood to breastfeed for 6 months. All women should be guided to plan for BF of their infants in the antenatal period (Marks et al, 2018). Ventura reported that, longer BFD predicted lower use of nonresponsive feeding practices during later childhood.…”
Section: Maternal Factors and Barriersmentioning
confidence: 99%
“…Infants whose parents agreed antenatally on BF only were more likely to have been breastfed for > 6 months. As well, interventions that promote BF to both mothers and husband which enable parents to reach agreement about intended feeding methods have the potential to increase both EIBF and EBFD (Marks et al, 2018).…”
Section: Clinical Practice Factors and Barriersmentioning
confidence: 99%